Penyuluhan Hukum Tentang Tindak Pidana Penghapusan Kekerasan Dalam Rumah Tangga - Hascaria Budi Prasetyo; Putut Hadi Suprayitno; Deddy Muharman; Lily Solichul Mukminah; Novellita Sicillia Anggraini; Aan Subekti; Moch. Azka Fuadi (Pusat Riset dan Inovasi Nasional, 2022)
The integrity and harmony of a happy, safe, secure and peaceful household is everyone's dream. Thus, every person in the household sphere in carrying out their rights and obligations must be based on religion. This needs to continue to be developed in order to build household integrity. To realize this wholeness and harmony, it really depends on each person in the household, especially the level of quality of behavior and self-control of each person in the household. The integrity and harmony of the household can be disrupted if the quality of self-control cannot be controlled, which in the end can result in domestic violence resulting in insecurity or injustice towards different people within the household. To prevent, protect victims and take action against perpetrators of domestic violence, the State and society are obliged to carry out prevention, protection and prosecution of perpetrators in accordance with the philosophy of Pancasila and the 1945 Constitution. For this reason, the Government has enacted Law Number 23 of 2004 concerning the Elimination of Domestic Violence so that every its citizens are protected. This law, apart from regulating the prevention, protection and recovery of victims of domestic violence, also specifically regulates violence that occurs in the household with elements of criminal acts that are different from criminal acts of abuse as regulated in the Law Code. Criminal. Apart from that, this Law also regulates the obligations of law enforcement officers, health workers, social workers, volunteer companions, or spiritual guides to protect victims so that they are more sensitive and responsive to household interests which from the start are directed at the integrity and harmony of the home. ladder.